2019
DOI: 10.1007/s12311-019-01074-w
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Modulation of Mesolimbic Dopamine Transmission Is Functionally Asymmetrical

Abstract: Cerebral and cerebellar hemispheres are known to be asymmetrical in structure and function, and previous literature supports that asymmetry extends to the neural dopamine systems. Using in vivo fixed-potential amperometry with carbon-fiber microelectrodes in anesthetized mice, the current study assessed hemispheric lateralization of stimulation-evoked dopamine in the nucleus accumbens (NAc) and the influence of the cerebellum in regulating this reward-associated pathway. Our results suggest that cerebellar out… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Here, we focused on the nucleus accumbens (NAc), a complex limbic structure that shares reward, motivation and affective functionality with the CB 51,52 . Stimulation of CB cortex or deep cerebellar nuclei (DCN) modulates levels of NAc dopamine --an important, but not exclusive, regulator of NAc functions [53][54][55][56][57][58][59] . However, how the CB connects to NAc is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focused on the nucleus accumbens (NAc), a complex limbic structure that shares reward, motivation and affective functionality with the CB 51,52 . Stimulation of CB cortex or deep cerebellar nuclei (DCN) modulates levels of NAc dopamine --an important, but not exclusive, regulator of NAc functions [53][54][55][56][57][58][59] . However, how the CB connects to NAc is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the electrical stimulation of the fastigial nucleus increased only the release of [ 3 H]-DA in the ipsilateral caudate nucleus (Nieoullon et al, 1978), and the electrical stimulation of the posterior interpositus nucleus increased the release of [ 3 H]-DA in ipsilateral SNpc and in the contralateral caudate nucleus while decreasing the release [ 3 H]-DA in the ipsilateral caudate nucleus (Nieoullon and Dusticier, 1980). In addition, the electrical stimulation of the mouse cerebellar dentate nucleus was elicited mainly in the contralateral nucleus accumbens (NAc), determining an asymmetrical and lateralized DA release (Figure 9; Holloway et al, 2019).…”
Section: Cerebellar-midbrain Dopaminergic Pathwaysmentioning
confidence: 98%
“…Finally, electrophysiological, pharmacological and immunohistochemical research studies investigated how different neurotransmitter systems, such as noradrenergic, cholinergic or dopaminergic system, can modulate the synaptic transmission and thereby influence the functional output through activation of specific cerebellar receptor subtypes (156)(157)(158)(159)(160)(161)(162)(163)(164)(165)(166).…”
Section: The Cognitive Emotional and Behavior Cerebellummentioning
confidence: 99%
“…However, lesion studies have shown the involvement of cerebellum in dopamine deficit-related neurological and psychiatric disorders, such as Parkinson's disease, schizophrenia, autism spectrum disorders, and drug addiction (158)(159)(160)(161). Moreover, data coming from invasive studies in animal and tractography observation in humans revealed relevant patterns of intracerebellar dopaminergic connectivity, such as between the DN and the cerebellar cortex, and extrinsic interconnections between the cerebellum and traditional dopaminergic areas of the brain, including the midbrain, the neostriatum, the neocortex (162)(163)(164)(165). These connections could represent part of the cerebellar projective circuits which allow the cerebellum to contribute to motor and cognitive functions (164,166).…”
Section: The Cognitive Emotional and Behavior Cerebellummentioning
confidence: 99%